DISLOCATION DENSITY INFLUENCE ON MOIRE PATTERN FORMATION - Mnatsakanyan, T. S.; Aloumyan, K. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
In the given work it is theoretically and experimentally stated that the decrease of dislocation density in a crystalline block of X-ray interferometer leads to the decrease of the frequency of moire fringes.